(untitled) (Pedagogy of Higher and Secondary Education, 2006)
The article shows the aesthetic feelings’ formation of scholars on art lessons exposes the research maintenance of efficacy of active forms and methods of education which were detached. The article renders the results of diagnostic of levels of aesthetic feeluigs’ formation using synthesis of arts.